Lecture matérialiste des Méditations cartésiennes - Anne Staquet (Les Dossiers du GRIHL)
Materialistic interpretation of the Cartesian MéditationsWhen, on rare occasions, we consider the materialistic nature of the Cartesian thinking, we systematically refer to scientific texts. In this perspective, more philosophical texts are not taken into consideration or are even ignored, as Hiram Caton showed it by discrediting the Méditations because they would only have been written to dupe the censure and buy a reputation for their author. They would therefore have no philosphical pertinence at all. But Descartes never stopped to insist on the importance of combining both writing types: the scientific one and the metaphysical one. For that reason, contrary to these considerations, I propose a materialistic interpretation (in the Leibnizian sense of the term) of the Méditations métaphysiques. To do so, with reference to the words of Descartes, I will start by showing how the philosopher uses the concealment in all of his works. I will show how the Cartesian dualism allows to constitute a materialism. I will finally show how proofs of the existence of God and the distinction between body and soul do not really contradict a materialistic interpretation of the Cartesian Méditations.